Impact of CEO Educational Background on Firm Financial Performance in Fashion Luxury Industry - CHENG, Jiamei (2020)
Fashion luxury industry is a field full of commercial interests and artistic pursuits at the same time. This paper examines the question of whether the firm financial performance is influenced by the educational background of CEO, and whether this relationship will be affected by other demographic characteristics. This paper applies the fix effected regression model to examine the impact of CEO educational degree (undergraduate, postgraduate and PHD) and type (MBA degree or non-MBA degree) on the firm financial performance. The panel dataset which includes 30 fashion luxury companies shows that only 34.7% of fashion companies have a CEO with an MBA degree. The empirical results show: (1) no significant relationship between CEO educational degree and firm financial performance; (2) firms with CEOs who have an MBA degree perform significantly better on financial performance than firms managed by CEOs with other kinds of educational types; (3) a strong negative relationship between CEO’s age and firm financial performance; (4) no significant association between CEO’s gender and firm performance; (5) a significant positive relationship between CEO’s tenure and firm financial performance; (6) the relationship between CEO educational type and firm financial performance rarely influenced by other demographic characteristics. Keywords: fashion luxury industry, financial performance, CEO educational background